Strategy in teaching writing in online teaching: A case study of SMA Taman Madya Ibu Pawiyatan Yogyakarta - Jayadi, Lukman (Journal of English Language and Pedagogy, 2021)
This Research aimed to: (1) to know the implemented strategies in teaching writing in online teaching at second-grade students of SMA Taman Madya IP Yogyakarta and (2) to know the difficulties of the teaching of teaching writing skill strategies at second-grade students of SMA Taman Madya IP Yogyakarta. The method of this study was case study research. The subject of the research was the English teacher at second Grade students of SMA Taman Madya IP Yogyakarta. The strategies teaching writing skills which to find the teaching writing process and difficulties in online teaching. The interview was conducted by English teacher after the strategy was applied in the teaching writing to the students. The observations were done by video recording. The finding that strategies in teaching writing in online teaching activity were (a) the strategy of vocabulary teaching online by using Power Point, (b) Zoom and Whats App, (c)Strategy of Teaching Grammar developed in You Tube using Google Classsroom and Teacher’s Strategy to Present grammar point using Zoom Meeting and Google-Classroom, (d) Strategy of teaching hand-writing using WhatsApp, (e) The strategy of teaching types of text implementing You Tube and google classroom. Strategy teaching Closing Activity, Teacher’s difficulties in using Online Teaching Media were that (1) the teacher did not operate Smartphone in online teaching because she was confused about all the menu systems on-screen, (2) when the teacher explained the materials internet connection occurs, (3) to see whether the students active online using the zoom. It was difficult for the teacher using online teaching.